The Influence of an Immersive-Collaborative Learning Unit on the Technology Acceptance of 5G and AR of Industrial Mechanic Students - Schäfers, Johannes; Temmen, Katrin (Proceedings of the 27th International Conference on Interactive Collaborative Learning (ICL2024), Volume 4)
Despite its status as a key enabling technology, the adoption of 5G in industry remains limited, mainly due to a lack of expertise, which can be addressed by incorporating 5G training into vocational schools. Since Augmented Reality (AR) faces similar challenges, it is used as the 5G application. This research aims to determine the extent to which a learning unit using 5G and AR for collaborative work can increase the intention to use these technologies in the vocational setting and gathers the factors that make up 5G acceptance. It is based on the Technology Acceptance Model 2 (TAM2). The sample includes 23 industrial mechanics students who participated in the developed learning unit. All items are scored on seven-tiered Likert scales (0 “totally disagree”; 6 “totally agree”). The results showed a non-significant change in behavioural intention to use 5G, with a mean of 4.95 (SD: 1.18) for the pre-test and 4.43 (SD: 1.68) for the posttest. The change in intention to use AR did not change significantly either, from 3.12 (SD: 1.38) at pre-test to 3.37 (SD: 1.16) at post-test. The factors Perceived Usefulness, Image, and Relevance had the lowest mean scores, indicating areas for targeted improvement. The significant change in Output Quality ratings is likely to reflect initial overestimation by students. The difference in Behavioural Intentions between 5G and AR suggests that AR may not be an effective technology for increasing 5G adoption in educational contexts. One recommendation is to address 5G in the learning unit not only indirectly.
Keywords: 5G; Key Technology; TAM · Augmented Reality; VET

More Efficient Techniques for Adaptively-Secure Cryptography - Niehues, David
Modern-day communication has become more and more digital. While this comes with many advantages such as a more efficient economy, it has also created more and more opportunities for various adversaries to manipulate communication or eavesdrop on it. The Snowden revelations in 2013 further highlighted the seriousness of these threats. To protect the communication of people, companies, and states from such threats, we require cryptography with strong security guarantees. Different applications may require different security properties from cryptographic schemes. For most applications, however, so-called adaptive security is considered a reasonable minimal requirement of security. Cryptographic schemes with adaptive security remain secure in the presence of an adversary that can corrupt communication partners to respond to messages of the adversaries choice, while the adversary may choose the messages based on previously observed interactions. While cryptography is associated the most with encryption, this is only one of many primitives that are essential for the security of digital interactions. This thesis presents novel identity-based encryption (IBE) schemes and verifiable random functions (VRFs) that achieve adaptive security as outlined above. Moreover, the cryptographic schemes presented in this thesis are proven secure in the standard model. That is without making use of idealized models like the random oracle model.
Keywords: public-key cryptography; lattices; pairings; verifiable random functions; identity-based encryption

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

Nonlinear waveguides for integrated quantum light source - Domeneguetti, Renato R.; Conradi, Hauke; Kleinert, Moritz; Kießler, Christian; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas Schou; Gehring, Tobias (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference)
We experimentally investigate the generation of continuous-wave optical squeezing from a titanium-indiffused lithium niobate waveguide resonator at low and high frequencies. The device promises integration with different platform chips for more complex optical systems.
Keywords: Optical systems; Polymer waveguides; Quantum key distribution; Quantum light sources; Squeezed states; Waveguides